Deflection enhancement of ferrite magnetic core-based microactuator - Pawinanto, Roer Eka; Mulyanti, Budi; Fauzan, Jahril Nur; Subandi, Ayub; Hasanah, Lilik; Pangestu, M. Assadillah; Yunas, Jumril (Institute of Advanced Engineering and Science, 2025)
Microactuators play a vital role in several microelectromechanical systems (MEMS) that generate forces or deflections necessary to accomplish functions such as scanning, tuning, manipulation, or delivery. Utilizing a ferrite magnetic core has shown the potential to enhance the deflection of the microactuator. However, the previous study presented a complex fabrication method with high power consumption unsuitable for micropump application. Herewith, we report the impact of ferrite core length on the deflection generated by a microactuator with a simple fabrication method. The deflection behavior shows that the corresponding magnetic core length is inverse to the deflection improvement. The force reduction generated led by a longer magnetic core because of the farther distance to the coil. Our study can be used as a reference to support the development of micropump or active micromixer devices, which require compact devices with simple fabrication and high deflection, achieving ultra-high flow rate and high mixing index.